Om trångboddhet: Hur storleken på våra bostäder blev ett välfärdsproblem (Sociologisk Forskning, 2013)
About crowding – How the size of our dwellings became a welfare problemHousing policy documents have traditionally been studied by political scientists, resulting in a lack of interest in the private aspects of housing policy. Hence, this paper uses the example of crowding standards to examine how a previously private matter, the size of our dwelling, became a concern of the state. Official governmental documents are analyzed with the help of discourse theory, working on the supposition that the need of the population and the framing of a problem changes over time. The first official standard of crowding, formulated in 1946 argue for larger dwelling size in order to increase the size and quality of the Swedish population. The second standard, formulated in 1965, is based on the assumption that the population, defined as consumers, demands larger sized homes. The final standard, formulated in 1975, claims that larger sized homes is a social right.